Efficiency Analysis of Dye Sensitized Solar Cells (DSSC) Based on Natural Dyes using Single and Double Layer TiO 2 Photoelectrodes - Nurul Amalia Silviyanti; Nurrima Puspitasari; Endarko Endarko (Journal of Engineering, Electrical and Informatics, 2025)
Dye sensitized solar cells based on natural dyes have been successfully fabricated using single layer and double layer photoelectrodes of TiO2. Single layer photoelectrode has been fabricated with TiO2 nanoparticles (14 -40 nm).Meanwhile the double layer photoelectrodes have been fabricated with TiO2 nanoparticles (14 -40 nm) as bottom layer and subnano-particles (120 - 140nm) as top layer.All samples got treatment for the same period of submersion with mixed three natural dyes that contains of chlorophyll, curcumin and anthocyanin. Gel electrolyte based on PEG 1000 has utilized for increasing the lifetime of DSSC. This study was to investigate the characteristics of DSSC that have fabricated from single and double layer TiO2 photoelectrodes. The result showed that the double layer photoelectrodes is generally better than the single layer photoelectrode, with the result efficiency 0.38% and 0,25%, respectively. The open circuit voltage (Voc), short circuit current (Isc), maximum power (Pmax) and Fill Factor (FF) were measured at 310 mV, 638 µA, 71,5 µW and 36,18%, respectively, for the double layer TiO2 photoelectrodes. Meanwhile the open circuit voltage (Voc), short circuit current (Isc), maximum power (Pmax), and Fill Factor (FF) are 330 mV, 580 µA, 46,94µW and 24,52%, respectively, were achieved for the single layer TiO2 photoelectrode.